Pelatihan Praktik Pembuatan Yoghurt Di MTs Baabussalam, Kecamatan Gading Rejo, Kabupaten Pringsewu, Provinsi Lampung - Nida Lidya Susanti; Devi Eka Lestari; Indriyani (CV. Multi Kreasi Media, 2025)
Conventional biotechnology is a topic in the science curriculum that is often delivered only theoretically in the classroom. This community service activity aimed to enhance students’ understanding and skills in applying biotechnology concepts through a yoghurt-making training at MTs Baabussalam, Gading Rejo Subdistrict, Pringsewu Regency, Lampung Province. The training was conducted on February, 19th, 2025, and attended by 28 students and two accompanying teachers. The stages of this activity included preparation, implementation, and closing. During the implementation phase, the activities carried out included a pre-test, a briefing session, demonstrations by the service team, hands-on practice by students, discussion and Q&A, and a post-test. The yoghurt was made by mixing pasteurized milk and plain yoghurt as a starter in a 1:4 ratio, followed by fermentation for 1–2 days. Evaluation results showed a significant increase in the students' average score from 53.2 (pre-test) to 84.6 (post-test). Students also showed high enthusiasm during the practice and gained a more concrete understanding of the fermentation process. This activity demonstrates that a practice-based approach is effective in enhancing students' understanding while also introducing them to simple entrepreneurship through fermented products.